The Collagen-binding Leech Products rLAPP and Calin Prevent both von Willebrand Factor and α2β1 (GPIa/IIa)-I-domain Binding to Collagen in a Different Manner - Depraetere, H.; Kerekes, A.; Deckmyn, H. (Thrombosis and Haemostasis, 1999)
Calin and rLAPP are two natural inhibitors that are able to inhibit the vWF-binding and platelet adhesion to collagen both under static and flow conditions. In this study we demonstrate that both rLAPP and Calin prevent α2I-domain binding to human collagen type I with an IC50 of 5 μg/ml. However, although both vWF and α2I-domain binding to collagen is prevented by rLAPP and Calin, the latter two do not bind to the same collagen site since Calin only partially could compete with rLAPP for binding to collagen. Also vWF and the α2I-domain were unable to compete completely with each other for the binding to collagen. So the following hypothesis can be made: the binding sites of vWF and of the α2I-domain on human collagen type I are different but close to each other since rLAPP could inhibit both interactions, and thus should bind to an overlapping epitope. The Calin preparation on the other hand may still contain two active principles, one interfering with vWF-binding, the other with the α2I-domain-binding to collagen.